The need and rise of secondary smart cities: a case of Bhuj. Issue 1 (November 2020) - Doshi, S; Roy, P; Iyer, M; Mishra, G
Abstract: With the Fourth Industrial Revolution, cities are being acknowledged by various city leaders, urbaniste, and urban enthusiasts as the employing giants of the world. Urbanization has led to people migrating to urban nodes, not only from rural to urban but from urban to urban areas as well, thereby, leading to a significant influx of migrants. This is more evident in the fast-growing secondary cities that are becoming the new job centres. However, while incorporating a Master Planning and Development Planning approach, there is a consequential crisis of resource and infrastructure while accommodating the new residents. Coupled with the rise of health emergencies such as cholera and now, recently, COVID-19, the cities are calling for better management and administration of resources, especially water resources in the cities of the global south. As envisioned in various debates, 2/3rd of the world's population shall reside in urban areas. Self-sufficiency and resource management are going to be prime concerns soon. In Bhuj, the district headquarters of Kutch in Gujarat, India, a water crisis is already evident, and the city will need to cope up with this increasing demand for the better. This provides a potential for the development of a framework that can lay out a more efficient system for resource provision and administration. The Smart Cities initiative can act as a tool for bridging the gaps between technology and sociology. This study, therefore, acknowledges the potential by understanding the concept of smart cities, the application, and nuances of the concept in India, where the concept has started to hold ground as a notion in the form of Government-led Smart City Competitions. This research aims to study the various frameworks and mechanisms related to smart cities and Smart Cities Mission, and how the different verticals of the framework, i.e. physical, social, economic, and governance points of view, are co-dependent on each other. The study also acknowledges the existing arguments surrounding the potential of secondary cities like Bhuj, and how the efficiency in terms of water sensitivity can be improved optimally by bringing all stakeholders to the table and trigger discussions to provide a better quality of life to the citizens. The paper aims at urban enthusiasts, academicians, citizen groups, and decision-makers to dive into the potentials of the water-sensitive aspects of the Smart Cities Mission and how secondary fast-growing cities can gain some headway with this.